On Simples, Attributed to Dioscorides : Introduction, Translation, Concordances - Fitch, John G. (Studies in Ancient Medicine, 2022)
On Simples , a medicinal text of the first century A.D., is attributed in the manuscripts to the famous Dioscorides. In a remarkable piece of detective work, Professor Fitch establishes that its alphabetical sequences of medications, ignored by earlier scholars, are conclusive proof that the attribution cannot be correct. He also shows that these sequences provide evidence about the content of earlier, now lost, works, including perhaps the Rhizotomikon of Crateus. This is the first English translation of On Simples . With its exhaustive concordances and indices, it will make the work accessible to readers interested in ancient medicine, and will facilitate future research.